A metrological approach to improve accuracy and reliability of ammonia measurements in ambient air. (5th October 2016) - Pogány, Andrea; Balslev-Harder, David; Braban, Christine F; Cassidy, Nathan; Ebert, Volker; Ferracci, Valerio; Hieta, Tuomas; Leuenberger, Daiana; Martin, Nicholas A; Pascale, Céline; Peltola, Jari; Persijn, Stefan; et al.
Abstract: The environmental impacts of ammonia (NH3 ) in ambient air have become more evident in the recent decades, leading to intensifying research in this field. A number of novel analytical techniques and monitoring instruments have been developed, and the quality and availability of reference gas mixtures used for the calibration of measuring instruments has also increased significantly. However, recent inter-comparison measurements show significant discrepancies, indicating that the majority of the newly developed devices and reference materials require further thorough validation. There is a clear need for more intensive metrological research focusing on quality assurance, intercomparability and validations. MetNH3 (Metrology for ammonia in ambient air) is a three-year project within the framework of the European Metrology Research Programme (EMRP), which aims to bring metrological traceability to ambient ammonia measurements in the 0.5–500 nmol mol −1 amount fraction range. This is addressed by working in three areas: (1) improving accuracy and stability of static and dynamic reference gas mixtures, (2) developing an optical transfer standard and (3) establishing the link between high-accuracy metrological standards and field measurements. In this article we describe the concept, aims and first results of the project.